2004
DOI: 10.1007/s00464-003-9143-4
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve for a colonoscopy simulator in the absence of any feedback: No feedback, no learning

Abstract: This study demonstrates that in the absence of feedback, it is not possible to improve performance on the HT Immersion Medical Colonoscopy Simulator. Thus, there is no learning curve for the machine. The information from this study is vital for using the simulators in training and assessment because any improvement in learning curves shown after training on simulators can be presumed to be due to learning the procedure and not the simulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(114 citation statements)
references
References 8 publications
3
110
0
1
Order By: Relevance
“…The considerable decrease in the pain-related parameters could mean that they also gained understanding of the factors and actions that cause pain or discomfort for the patient during flexible endoscopy. This contrasts with the results of studies by Mahmood and Darzi [22], and Datta et al [24]. The greater number of exercises, the combination of different exercise types, or the influence of knowledge of results could contribute to this difference.…”
Section: Performance Of the Novicesmentioning
confidence: 59%
See 1 more Smart Citation
“…The considerable decrease in the pain-related parameters could mean that they also gained understanding of the factors and actions that cause pain or discomfort for the patient during flexible endoscopy. This contrasts with the results of studies by Mahmood and Darzi [22], and Datta et al [24]. The greater number of exercises, the combination of different exercise types, or the influence of knowledge of results could contribute to this difference.…”
Section: Performance Of the Novicesmentioning
confidence: 59%
“…The validity of the different systems for lower gastrointestinal endoscopy skills has been studied previously [7,8,12,15,[17][18][19][20][21][22][23][24][25]. However, most of these studies did not focus on the basic tasks first, but included multiple (complex) tasks or used a relative small numbers of participants.…”
mentioning
confidence: 99%
“…We used distributed practice in our study as the data fairly consistently support its superiority for motor skill acquisition [30], however there is still debate on the ideal timing of the training sessions. Performance feedback is another essential concept for simulator skill acquisition [40, [84][85][86]. Relevant to our study is the debate on whether concurrent feedback, provided during task performance, or summative feedback, provided at the end of task performance, is best.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies confirm the importance of feedback in simulator training. Mahmood et al 12 showed that in the absence of feedback there was no improvement in performance on the colonoscopy simulator, whereas Boyle et al 13 demonstrated that the provision of standardized proxi mate feedback during laparoscopic colectomy simulator training was associated with significantly fewer errors and an improved learning curve.…”
Section: Discussionmentioning
confidence: 99%